Coronary artery bypass grafting versus percutaneous coronary intervention with stenting for multivessel coronary artery disease without left main coronary disease:reconstructed individual patient data. (3rd October 2022) - Chew, N W S; Ng, C H; Xiao, J L; Chan, K H; Loh, P H; Low, A; Lee, C H; Tan, H C; Chan, M Y
Abstract: Background and aims: Data are emerging on 10-year mortality comparing coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) with stenting for multivessel disease (MVD) without left main (LM) involvement. We conducted an updated two-stage meta-analysis using reconstructed individual patient data to compare long-term mortality between CABG and PCI for patients with MVD without significant LM coronary disease. Methods: Medline and Embase databases were searched for articles comparing CABG with PCI for MVD. A two-stage meta-analysis was conducted using reconstructed patient level survival data for all-cause mortality with subgroups by SYNTAX score. The shared-frailty and stratified Cox models were fitted to compare survival endpoints. Results: We screened 1496 studies and included six randomized controlled trials with 7181 patients. PCI was associated with greater 10-year all-cause mortality risk (HR: 1.282, CI: 1.118–1.469, p<0.001) compared with CABG. In patients with low SYNTAX score, 10-year all-cause mortality after PCI was comparable to CABG (HR: 1.102, 0.822–1.479, p=0.516). However, in patients with moderate to high SYNTAX score, 10-year all-cause mortality was significantly higher after PCI compared with CABG (HR: 1.444, 1.122–1.858, p<0.001; HR: 1.856, 1.380–2.497, p<0.001 respectively). Conclusion: This updated reconstructed individual patient-data meta-analysis revealed a sustained lower cumulative all-cause mortality of CABG over PCI for multivessel disease without LM involvement. Funding Acknowledgement: Type of funding sources: None.